Soil-to-Plant Transfer of Naturally Occurring Radionuclides in West Africa: Mechanisms, Transfer Factors, Food-Chain Contamination, And Human Health Implications (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Naturally occurring radionuclides (NORMs), including uranium-238 (238U), thorium-232 (232Th), radium-226 (226Ra), and potassium-40 (40K), are widely found in terrestrial ecosystems and are a significant source of environmental radiation exposure. Their movement from soil to plants is a crucial process through which radionuclides enter the food chain, leading to internal radiation doses in humans. This review summarizes the current understanding of the environmental distribution, mechanisms of soil-to-plant transfer, transfer factors, and the radiological consequences of naturally occurring radionuclides in West Africa Peer-reviewed papers from major scientific databases were used to undertake a structured literature review, with a focus on studies reporting radiological risk assessments, soil-to-plant transfer factors, and radioactive activity concentrations. The research that is now available suggests that a variety of factors, including soil physicochemical features, radionuclide speciation, plant traits, climate, and agricultural methods, influence the uptake of radionuclides by plants. Due to its vital biological role, potassium-40 often demonstrated the largest transfer to crops, while radionuclides from the uranium and thorium family showed relatively lesser mobility but were nonetheless significant contributors to long-term internal radiation exposure. The analysis also shows that while quantitative studies on soil-to-plant transfer are still scarce and spatially unequal, environmental radioactivity evaluations dominate research in West Africa. The majority of published studies are from Nigeria and Ghana, however there are still significant knowledge gaps in many other West African nations. Regional radiological risk assessment is made questionable by the absence of long-term environmental monitoring, locally determined transfer factor databases, and standardized procedures. Harmonized radioecological studies, the creation of region-specific transfer factors for important staple crops, integrated food-chain studies, and ongoing environmental monitoring should be the top priorities for future study. By filling in these gaps, West African decision-making on public health, food safety, and environmental radiation protection will be strengthened and exposure assessment accuracy will increase.